Transplantation of the heart after circulatory death of the donor: time for a change in law?. Issue 6 (21st September 2015) - Tibballs, James; Bhatia, Neera
Summary: Australia has a shortfall in donated hearts for transplantation. Hearts are usually procured from brain dead donors, but procurement from circulatory dead donors is a potential additional source. However, heart transplantation after circulatory death of the donor may not conform to the dead donor rule. An amendment in law is required to permit heart procurement for transplantation after circulatory death.